High-strength high-thermal-conductivity silicon carbide composite material and preparation method thereof

By using a specific proportion of silicon carbide fine powder, diamond powder, single silicon powder, nano -copper powder, nano -graphite powder, and sintering auxiliary agent, combined with spray drying and induction sintering technology to prepare high -intensity and high -heated silicon carbide composite materials, solved the solution The problems of high energy consumption, low bending strength, low fracture toughness, and low thermal conductivity have achieved high -efficiency and low energy consumption preparation processes and excellent mechanics and thermal conductivity.

CN119371207AActive Publication Date: 2025-01-28WUHAN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411406284.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-28
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing silicon carbide materials have high energy consumption during the preparation process, and have problems such as low flexural strength, low fracture toughness and low thermal conductivity.

Method used

Use 50 ~ 60WT % of silicon carbide fine powder, 28 to 32WT % diamond powder, 5-10WT % single -quality silicon powder, 2 to 5WT % of nano -copper powder, 2 to 4WT % nano graphite powder and 1 to 3WT % % The sintering aid is raw material, and high -strength high -heat -conducting silicon composite materials are prepared by spraying and induction sintering technology.

Benefits of technology

It significantly improves the thermal conductivity, bending strength, and fracture toughness of high -strength high -intensity and high silicon carbide composite materials, while reducing the energy consumption of the preparation process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. According to the technical scheme, silicon carbide fine powder, diamond powder, monatomic silicon powder, nano-copper powder, nano-graphite powder and a sintering aid serve as raw materials, deionized water is added, the raw materials are mixed and placed in a spray dryer for spray drying, and a mixture I is obtained; mixing the mixture I with a polyvinyl alcohol aqueous solution to obtain a mixture II; and putting the mixture II into a mold, carrying out compression molding, and maintaining the pressure to obtain a silicon carbide composite material green body. The silicon carbide composite material green body is placed in a graphite crucible, then the graphite crucible is placed in a vacuum induction furnace, and heating and heat preservation are conducted under the vacuum condition; and heating, preserving heat and cooling to obtain the high-strength and high-thermal-conductivity silicon carbide composite material. The preparation process is low in energy consumption, and the prepared high-strength and high-thermal-conductivity silicon carbide composite material is high in bending strength, fracture toughness and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon carbide materials, and specifically relates to a high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. Background Art

[0002] Silicon carbide materials have the advantages of high strength, high hardness, high thermal conductivity, wear resistance, corrosion resistance and good chemical stability, and are widely used in aviation, military industry, electronic devices and other fields. The carbon atoms and silicon atoms in silicon carbide are bound by strong covalent bonds. Its high bond energy leads to low self-diffusion coefficient of silicon carbide materials, sensitivity to cracks and defects, and poor reliability. With the rapid development of industries such as integrated circuits, semiconductor packaging materials and high-temperature heat exchangers, higher requirements have been put forward for the thermal conductivity and mechanical strength of silicon carbide materials, which has attracted the attention of technicians in this field.

[0003] The patented technology of "A large-size, high-strength graphene nanosheet / silicon carbide composite material and its preparation method (CN201810287961.3)" uses hot pressing and sintering to prepare silicon carbide composite materials with high bending strength and fracture toughness, but the sintering temperature reaches 2200°C and the sintering pressure reaches 80MPa, and the preparation process has high energy consumption.

[0004] The patented technology of "Silicon carbide ceramics and preparation methods thereof (CN202410039166.8)" improves the flexural strength and fracture toughness of silicon carbide ceramics by combining sintering aids with spark plasma sintering. However, the addition of sintering aids will lead to a decrease in the density of silicon carbide ceramics, making it difficult to simultaneously achieve improvements in both thermal conductivity and flexural strength of silicon carbide ceramics.

[0005] The patented technology "A silicon carbide material and its preparation method (CN202311723599.7)" uses organic matter as a binder. Although it reduces the temperature for preparing silicon carbide materials, the burning of organic matter at high temperatures produces pores, which has a negative impact on the thermal conductivity of silicon carbide materials.

[0006] The patented technology of "A high thermal conductivity silicon carbide material and its preparation method (CN202110135638.6)" introduces diamond into silicon carbide to enhance the thermal conductivity of the silicon carbide material, but the poor bonding between the two phases results in low bending strength and fracture toughness of silicon carbide.

[0007] In summary, the existing silicon carbide materials are limited by the composition and preparation method, the preparation process has high energy consumption, and the prepared silicon carbide materials have problems such as low bending strength, low fracture toughness and low thermal conductivity. Summary of the invention

[0008] The present invention aims to overcome the deficiencies of the prior art and has the object of providing a method for preparing a high-strength and high-thermal conductivity silicon carbide composite material with low energy consumption. The high-strength and high-thermal conductivity silicon carbide composite material prepared by the method has high bending strength, high fracture toughness and high thermal conductivity.

[0009] To achieve the above purpose, the specific steps of the technical solution adopted by the present invention are:

[0010] Step 1, using 50-60wt% of silicon carbide fine powder, 28-32wt% of diamond powder, 5-10wt% of elemental silicon powder, 2-5wt% of nano copper powder, 2-4wt% of nano graphite powder and 1-3wt% of sintering aid as raw materials, adding 100-150wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I.

[0011] Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100: (3-8) to obtain a mixture II; placing the mixture II in a mold, pressing and molding at 100-200 MPa, maintaining the pressure for 30-60 seconds, and obtaining a silicon carbide composite material green body.

[0012] Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -2 ~10 -1 Pa conditions, heating to 1100-1300°C at a heating rate of 60-80°C / min, and keeping warm for 10-30min; then heating to 1500-1700°C at a heating rate of 20-50°C / min, keeping warm for 20-40min, turning off the power of the vacuum induction furnace, cooling for 1-2h, and closing the circulating water valve to obtain a high-strength and high-thermal-conductivity silicon carbide composite material.

[0013] The SiC content in the silicon carbide fine powder is ≥99.0wt%; and the particle size of the silicon carbide fine powder is ≤1.0μm.

[0014] The purity of the diamond powder is ≥99.0wt%; the particle size of the diamond powder is ≤200μm.

[0015] The Si content in the elemental silicon powder is ≥99.9wt%; and the particle size of the elemental silicon powder is ≤1.0μm.

[0016] The content of Cu in the nano copper powder is ≥99.9wt%; and the particle size of the nano copper powder is ≤100nm.

[0017] The purity of the nano graphite powder is ≥99.9wt%; the particle size of the nano graphite powder is ≤400nm.

[0018] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.2:1.

[0019] The peristaltic pump speed of the spray dryer is 40-60 r / min, the pneumatic speed of the atomizer of the spray dryer is 20000-25000 r / min, the inlet temperature of the spray dryer is 150-200°C, and the outlet temperature of the spray dryer is 60-120°C.

[0020] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:

[0021] (1) The present invention gives full play to the high thermal conductivity of diamond and significantly improves the thermal conductivity of the high-strength and high-thermal conductivity silicon carbide composite material; the mixture I prepared by combining the spray granulation technology has good flowability and uniformity, improves the distribution uniformity of diamond and the density of the material in the high-strength and high-thermal conductivity silicon carbide composite material, and the prepared high-strength and high-thermal conductivity silicon carbide composite material has excellent thermal conductivity.

[0022] (2) The elemental silicon powder used in the present invention reacts with nano-copper powder and nano-graphite during the heat treatment process to form copper-silicon alloy and silicon carbide, respectively, thereby improving the bonding between diamond and the matrix, and effectively enhancing the flexural strength and fracture toughness of the high-strength and high-thermal conductivity silicon carbide composite material; the nano-graphite removes oxygen-containing impurities in the silicon carbide raw material and repairs microscopic morphological defects, thereby synergistically improving the thermal conductivity and flexural strength of the high-strength and high-thermal conductivity silicon carbide composite material. Therefore, the prepared high-strength and high-thermal conductivity silicon carbide composite material has high thermal conductivity, high flexural strength and high fracture toughness.

[0023] (3) The present invention adopts induction sintering technology, which has a fast heating rate and a short insulation time; in particular, the strict limitation of the power and heating time of the induction sintering process is conducive to the uniform growth of grains in the high-strength and high-thermal conductivity silicon carbide composite material, which not only greatly reduces energy consumption, but also improves the density and mechanical properties of the high-strength and high-thermal conductivity silicon carbide composite material. Therefore, the preparation process of the present invention has low energy consumption, and the prepared high-strength and high-thermal conductivity silicon carbide composite material has high bending strength.

[0024] The high-strength and high-thermal-conductivity silicon carbide composite material prepared by the present invention is tested to have a volume density of 3.15 to 3.31 g / cm 3 , thermal conductivity is 305-320W / (m·K), flexural strength is greater than 400MPa, fracture toughness is greater than 7.50MPa·m 1 / 2 .

[0025] Therefore, the preparation process of the present invention has low energy consumption, and the prepared high-strength and high-thermal conductivity silicon carbide composite material has high bending strength, high fracture toughness and high thermal conductivity. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific implementation modes, but is not intended to limit the protection scope thereof.

[0027] A high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. The preparation method described in this specific embodiment is:

[0028] Step 1, using 50-60wt% of silicon carbide fine powder, 28-32wt% of diamond powder, 5-10wt% of elemental silicon powder, 2-5wt% of nano copper powder, 2-4wt% of nano graphite powder and 1-3wt% of sintering aid as raw materials, adding 100-150wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I.

[0029] Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100: (3-8) to obtain a mixture II; placing the mixture II in a mold, pressing and molding at 100-200 MPa, maintaining the pressure for 30-60 seconds, and obtaining a silicon carbide composite material green body.

[0030] Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -2 ~10 -1 Pa conditions, heating to 1100-1300°C at a heating rate of 60-80°C / min, and keeping warm for 10-30min; then heating to 1500-1700°C at a heating rate of 20-50°C / min, keeping warm for 20-40min, turning off the power of the vacuum induction furnace, cooling for 1-2h, and closing the circulating water valve to obtain a high-strength and high-thermal-conductivity silicon carbide composite material.

[0031] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.1-1.2:1.

[0032] The peristaltic pump speed of the spray dryer is 40-60 r / min, the pneumatic speed of the atomizer of the spray dryer is 20000-25000 r / min, the inlet temperature of the spray dryer is 150-200°C, and the outlet temperature of the spray dryer is 60-120°C.

[0033] In this specific implementation mode:

[0034] The SiC content in the silicon carbide fine powder is ≥ 99.0wt%, and the particle size of the silicon carbide fine powder is ≤ 1.0μm;

[0035] The purity of the diamond powder is ≥99.0wt%, and the particle size of the diamond powder is ≤200μm;

[0036] The Si content in the elemental silicon powder is ≥99.9wt%, and the particle size of the elemental silicon powder is ≤1.0μm;

[0037] The content of Cu in the nano copper powder is ≥99.9wt%, and the particle size of the nano copper powder is ≤100nm;

[0038] The purity of the nano graphite powder is ≥99.9wt%, and the particle size of the nano graphite powder is ≤400nm.

[0039] This will not be described in detail in the embodiments.

[0040] Example 1

[0041] A high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. The preparation method described in this embodiment is:

[0042] Step 1, using 50wt% of silicon carbide fine powder, 28wt% of diamond powder, 10wt% of elemental silicon powder, 5wt% of nano copper powder, 4wt% of nano graphite powder and 3wt% of sintering aid as raw materials, adding 100wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I.

[0043] Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100:3 to obtain a mixture II; placing the mixture II in a mold, pressing it under 100 MPa, and maintaining the pressure for 30 seconds to obtain a silicon carbide composite material green body.

[0044] Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -1 Pa conditions, heated to 1100°C at a heating rate of 60°C / min, and kept warm for 10 minutes; then heated to 1500°C at a heating rate of 20°C / min, kept warm for 20 minutes, turned off the power of the vacuum induction furnace, cooled for 1 hour, and closed the circulating water valve to obtain a high-strength and high thermal conductivity silicon carbide composite material.

[0045] In this embodiment:

[0046] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.1:1.

[0047] The peristaltic pump speed of the spray dryer is 40r / min, the pneumatic speed of the atomizer of the spray dryer is 20000r / min, the inlet temperature of the spray dryer is 150°C, and the outlet temperature of the spray dryer is 60°C.

[0048] The high-strength and high-thermal-conductivity silicon carbide composite material prepared in this embodiment was tested: the volume density was 3.15 g / cm 3 ; Thermal conductivity is 312W / (m·K); Flexural strength is 410MPa; Fracture toughness is 7.70MPa·m 1 / 2 .

[0049] Example 2

[0050] A high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. The preparation method described in this embodiment is:

[0051] Step 1, using 52wt% of silicon carbide fine powder, 32wt% of diamond powder, 7wt% of elemental silicon powder, 4wt% of nano copper powder, 3wt% of nano graphite powder and 2wt% of sintering aid as raw materials, adding 120wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I.

[0052] Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100:5 to obtain a mixture II; placing the mixture II in a mold, pressing and molding at 150 MPa, maintaining the pressure for 40 seconds, and obtaining a silicon carbide composite material green body.

[0053] Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -1 Pa conditions, heated to 1200°C at a heating rate of 70°C / min, and kept warm for 20 minutes; then heated to 1600°C at a heating rate of 30°C / min, kept warm for 30 minutes, turned off the power of the vacuum induction furnace, cooled for 1.5 hours, and closed the circulating water valve to obtain a high-strength and high thermal conductivity silicon carbide composite material.

[0054] In this embodiment:

[0055] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.1:1.

[0056] The peristaltic pump speed of the spray dryer is 50 r / min, the pneumatic speed of the atomizer of the spray dryer is 22000 r / min, the inlet temperature of the spray dryer is 160°C, and the outlet temperature of the spray dryer is 80°C.

[0057] The high-strength and high-thermal-conductivity silicon carbide composite material prepared in this embodiment was tested: the volume density was 3.22 g / cm 3 ; Thermal conductivity is 320W / (m·K); Flexural strength is 420MPa; Fracture toughness is 7.96MPa·m 1 / 2 .

[0058] Example 3

[0059] A high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. The preparation method described in this embodiment is:

[0060] Step 1, using 55wt% of silicon carbide fine powder, 31wt% of diamond powder, 6wt% of elemental silicon powder, 3wt% of nano copper powder, 3wt% of nano graphite powder and 2wt% of sintering aid as raw materials, adding 130wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I.

[0061] Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100:7 to obtain a mixture II; placing the mixture II in a mold, pressing it under 180 MPa, and maintaining the pressure for 50 seconds to obtain a silicon carbide composite material green body.

[0062] Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -2 Pa conditions, heated to 1200°C at a heating rate of 70°C / min, and kept warm for 25 minutes; then heated to 1650°C at a heating rate of 40°C / min, kept warm for 35 minutes, turned off the power of the vacuum induction furnace, cooled for 1.2 hours, and closed the circulating water valve to obtain a high-strength and high thermal conductivity silicon carbide composite material.

[0063] In this embodiment:

[0064] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.1:1.

[0065] The peristaltic pump speed of the spray dryer is 50 r / min, the pneumatic speed of the atomizer of the spray dryer is 23000 r / min, the inlet temperature of the spray dryer is 180°C, and the outlet temperature of the spray dryer is 100°C.

[0066] The high-strength and high-thermal-conductivity silicon carbide composite material prepared in this embodiment was tested: the volume density was 3.24 g / cm 3; Thermal conductivity is 316W / (m·K); Flexural strength is 440MPa; Fracture toughness is 8.12MPa·m 1 / 2 .

[0067] Example 4

[0068] A high-strength and high-thermal-conductivity silicon carbide composite material and a preparation method thereof. The preparation method described in this embodiment is:

[0069] Step 1, using 60wt% of silicon carbide fine powder, 30wt% of diamond powder, 5wt% of elemental silicon powder, 2wt% of nano copper powder, 2wt% of nano graphite powder and 1wt% of sintering aid as raw materials, adding 150wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I.

[0070] Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100:8 to obtain a mixture II; placing the mixture II in a mold, pressing it at 200 MPa, and maintaining the pressure for 60 seconds to obtain a silicon carbide composite material green body.

[0071] Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -2 Pa conditions, heated to 1300°C at a heating rate of 80°C / min, and kept warm for 30 minutes; then heated to 1700°C at a heating rate of 50°C / min, kept warm for 40 minutes, turned off the power of the vacuum induction furnace, cooled for 2 hours, and closed the circulating water valve to obtain a high-strength and high thermal conductivity silicon carbide composite material.

[0072] In this embodiment:

[0073] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.2:1.

[0074] The peristaltic pump speed of the spray dryer is 60r / min, the pneumatic speed of the atomizer of the spray dryer is 25000r / min, the inlet temperature of the spray dryer is 200°C, and the outlet temperature of the spray dryer is 120°C.

[0075] The high-strength and high-thermal-conductivity silicon carbide composite material prepared in this embodiment was tested: the volume density was 3.31 g / cm 3 ; Thermal conductivity is 305W / (m·K); Flexural strength is 450MPa; Fracture toughness is 8.26MPa·m 1 / 2 .

[0076] Compared with the prior art, this specific implementation has the following positive effects:

[0077] (1) The present invention gives full play to the high thermal conductivity of diamond and significantly improves the thermal conductivity of the high-strength and high-thermal conductivity silicon carbide composite material; the mixture I prepared by combining the spray granulation technology has good flowability and uniformity, improves the distribution uniformity of diamond and the density of the material in the high-strength and high-thermal conductivity silicon carbide composite material, and the prepared high-strength and high-thermal conductivity silicon carbide composite material has excellent thermal conductivity.

[0078] (2) The elemental silicon powder used in the present invention reacts with nano-copper powder and nano-graphite during the heat treatment process to form copper-silicon alloy and silicon carbide, respectively, thereby improving the bonding between diamond and the matrix, and effectively enhancing the flexural strength and fracture toughness of the high-strength and high-thermal conductivity silicon carbide composite material; the nano-graphite removes oxygen-containing impurities in the silicon carbide raw material and repairs microscopic morphological defects, thereby synergistically improving the thermal conductivity and flexural strength of the high-strength and high-thermal conductivity silicon carbide composite material. Therefore, the prepared high-strength and high-thermal conductivity silicon carbide composite material has high thermal conductivity, high flexural strength and high fracture toughness.

[0079] (3) The present invention adopts induction sintering technology, which has a fast heating rate and a short insulation time; in particular, the strict limitation of the power and heating time of the induction sintering process is conducive to the uniform growth of grains in the high-strength and high-thermal conductivity silicon carbide composite material, which not only greatly reduces energy consumption, but also improves the density and mechanical properties of the high-strength and high-thermal conductivity silicon carbide composite material. Therefore, the preparation process of the present invention has low energy consumption, and the prepared high-strength and high-thermal conductivity silicon carbide composite material has high bending strength.

[0080] The high-strength and high-thermal-conductivity silicon carbide composite material prepared by the present invention is tested to have a volume density of 3.15 to 3.31 g / cm 3 ; Thermal conductivity is 305-320W / (m·K); Flexural strength is greater than 400MPa; Fracture toughness is greater than 7.50MPa·m 1 / 2 .

[0081] The performance indicators involved in this specific implementation method are measured according to the following standards: the bulk density is measured according to the GB / T2999-2016 standard; the thermal conductivity is measured according to the GB / T5990-2021 standard; the flexural strength is measured according to the GB / T6569-2006 standard; and the fracture toughness is measured according to the GB / T 23806-2009 standard.

[0082] Therefore, the preparation process of this specific embodiment has low energy consumption, and the prepared silicon carbide composite material has high bending strength, high fracture toughness and high thermal conductivity.

Claims

1. A method for preparing a high-strength and high-thermal-conductivity silicon carbide composite material, characterized in that The steps of the preparation method are: Step 1, using 50-60wt% of silicon carbide fine powder, 28-32wt% of diamond powder, 5-10wt% of elemental silicon powder, 2-5wt% of nano copper powder, 2-4wt% of nano graphite powder and 1-3wt% of sintering aid as raw materials, adding 100-150wt% of deionized water to the raw materials, mixing to obtain a mixed slurry; placing the mixed slurry in a spray dryer, spray drying, to obtain a mixture I; Step 2, mixing the mixture I and the polyvinyl alcohol aqueous solution with a mass concentration of 5% in a mass ratio of 100: (3-8) to obtain a mixture II; placing the mixture II in a mold, pressing and molding at 100-200 MPa, and maintaining the pressure for 30-60 seconds to obtain a silicon carbide composite material green body; Step 3: Place the green silicon carbide composite material in a graphite crucible, then place the graphite crucible containing the green silicon carbide composite material in a vacuum induction furnace, open the circulating water valve, and heat the furnace at a vacuum degree of 10 -2 ~10 -1 Pa conditions, heating to 1100-1300°C at a heating rate of 60-80°C / min, and keeping warm for 10-30min; then heating to 1500-1700°C at a heating rate of 20-50°C / min, keeping warm for 20-40min, turning off the power of the vacuum induction furnace, cooling for 1-2h, and closing the circulating water valve to obtain a high-strength and high-thermal-conductivity silicon carbide composite material.

2. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The SiC content in the silicon carbide fine powder is ≥99.0wt%; and the particle size of the silicon carbide fine powder is ≤1.0μm.

3. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The purity of the diamond powder is ≥99.0wt%; the particle size of the diamond powder is ≤200μm.

4. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The Si content in the elemental silicon powder is ≥99.9wt%; and the particle size of the elemental silicon powder is ≤1.0μm.

5. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The content of Cu in the nano copper powder is ≥99.9wt%; and the particle size of the nano copper powder is ≤100nm.

6. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The purity of the nano graphite powder is ≥99.9wt%; the particle size of the nano graphite powder is ≤400nm.

7. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The sintering aid is a mixture of yttrium oxide and lanthanum oxide, and the molar ratio of yttrium oxide to lanthanum oxide is 1.1-1.2:

1.

8. The method for preparing the high-strength and high-thermal-conductivity silicon carbide composite material according to claim 1, characterized in that The peristaltic pump speed of the spray dryer is 40-60 r / min, the pneumatic speed of the atomizer of the spray dryer is 20000-25000 r / min, the inlet temperature of the spray dryer is 150-200°C, and the outlet temperature of the spray dryer is 60-120°C.

9. A high-strength and high-thermal-conductivity silicon carbide composite material, characterized in that The high-strength and high-thermal-conductivity silicon carbide composite material is a high-strength and high-thermal-conductivity silicon carbide composite material prepared by the method for preparing a high-strength and high-thermal-conductivity silicon carbide composite material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • A large-size, high-strength graphene nanosheet / silicon carbide composite material and its preparation method

    CN108585875B

  • High-thermal-conductivity silicon carbide material and preparation method thereof

    CN112939604A

  • Silicon carbide material and preparation method thereof

    CN117756532A

  • Silicon carbide ceramics and their preparation methods

    CN117964373B

  • Preparation methods of diamond / silicon carbide prefabricated part and diamond / silicon carbide / aluminium compound material

    CN108821775A

Cited By

  • Diamond reinforced silicon carbide slurry, porous composite material and preparation method of porous composite material

    CN121318526A